Comparison of Efficacy of Conventional Triple Therapy and Non Bismuth Quadruple Therapy for Helicobacter Pylori Eradication - Muhammad Sohail, Muhammad Fahim, Fahim Ullah Khan, Muhammad Sajjad Khan, Shakeel Akhter, Muhammad Shahab, Sundus Naeem, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the efficacy of conventional triple therapy and non bismuth quadruple therapy for helicobacter pylori eradication. Setting: Gastroenterology Department, Lady Reading Hospital Peshawar. Study Design: Randomized control trial. Duration: 6 months 15th August, 2018 to 15th February 2019. Materials and Methods: In this study a total of 111 patients were observed. Patients were put in two groups, group A triple Helicobacter pylori eradication therapy and group B non-bismuth quadruple Helicobacter pylori eradication therapy. Randomization of patients to either treatment group was done through lottery method. All patients were worked up with detailed history and clinical examination to look for any known allergy to drugs used in this study, to document any comorbidity and to exclude alarm features, baseline investigations including complete blood count, Random blood sugar, liver function tests and renal function tests. H pylori stool antigen was reported from Lady Reading Hospital laboratory at time of inclusion and four weeks after completion of therapy. The purpose and benefits of study was explained to patients and written consent for participation in study was obtained. Patients were asked on follow up about adherence to the treatment. Results: In this study mean age in Group A was 44 years with SD ± 2.77. Whereas mean age in Group B was 42 years with SD ± 3.12. In Group A 55% patients were male and 45% patients were female. Where as in Group B 58% patients were male and 42% patients were female. More over Group A (triple Helicobacter pylori eradication therapy) was effective in 75% patients. Where as Group B (non-bismuth quadruple Helicobacter pylori eradication therapy) was effective in 94% patients and was not effective in 6% patients. Conclusion: Our study concludes that non bismuth quadruple therapy is more effective than triple therapy in the treatment of Helicobacter pylori eradication. Keywords: Conventional triple therapy, Non-bismuth quadruple therapy, Helicobacter pylori eradication